Frequent 7q gains in flow cytometric multiploid/hypertetraploid breast carcinomas: a study of chromosome imbalances by comparative genomic hybridisation. Issue 4 (3rd February 2006) - Pinto, A E; Roque, L; Rodrigues, R; André, S; Soares, J
Abstract : Objective: To investigate underlying genetic events associated with complex DNA ploidy breast carcinomas. Methods: Screening for chromosome imbalances was carried out using comparative genomic hybridisation (CGH) in 14 frozen samples of tumour from a series of 13 breast cancer patients with multiploid (n = 11) and hypertetraploid (n = 2) tumours. They had previously been analysed by DNA flow cytometry and also assessed immunohistochemically for p53 tissue expression. Ploidy status was determined on frozen samples using the Multicycle software program. Results: The total number of copy gains (n = 242) was significantly greater than the number of copy losses (n = 51). The mean (SD) number of gains per sample was 17.3 (5.7), and of losses, 3.6 (4.2) (p = 0.0001). Gains of chromosomal regions at 1q (14/14; 100%), 7q (12/14; 85.7%), and 3q (11/14; 78.6%), as well as 1p, 2q, 5p, 8q, and 13q (10/14; 71.4%) were the most frequent aberrations in this series. Losses were most commonly found on 17p (5/14; 35.7%). Three patients dying of the disease had tumours with high level amplifications at 1q12-qter, 3q22–q25, and 8q22–q23 regions. Six cases had p53 overexpression, of whom four showed 12q gains and two showed 17p losses. Conclusions: There is a very high incidence of genetic aberrations, mainly related to chromosomal gains, in this subgroup of aneuploid breast cancer patients, associated with a poor clinical outcome. The 7q locus, not previously reported as showing frequent changes in breast cancer, was found to be a potential site for some candidate oncogenes.